Stereotactic body radiotherapy plus pembrolizumab and trametinib versus stereotactic body radiotherapy plus gemcitabine for locally recurrent pancreatic cancer after surgical resection: an open-label, randomised, controlled, phase 2 trial. Issue 3 (March 2022) - Zhu, Xiaofei; Cao, Yangsen; Liu, Wenyu; Ju, Xiaoping; Zhao, Xianzhi; Jiang, Lingong; Ye, Yusheng; Jin, Gang; Zhang, Huojun
Summary: Background: There is paucity of investigations into immunotherapy or targeted therapy for postoperative locally recurrent pancreatic cancer. We aimed to assess the efficacy of stereotactic body radiotherapy (SBRT) plus pembrolizumab and trametinib in these patients. Methods: In this open-label, randomised, controlled, phase 2 study, participants were recruited from Changhai Hospital affiliated to the Naval Medical University, Shanghai, China. Eligible patients were aged 18 years or older with histologically confirmed pancreatic ductal adenocarcinoma characterised by mutant KRAS and positive immunohistochemical staining of PD-L1, Eastern Cooperative Oncology Group performance status of 0 or 1, and documented local recurrence after surgery followed by chemotherapy (mFOLFIRINOX [ie, 5-fluorouracil, oxaliplatin, irinotecan, and folinic acid] or 5-fluorouracil). Eligible participants were randomly assigned (1:1) using an interactive voice or web response system, without stratification, to receive SBRT with doses ranging from 35–40 Gy in five fractions, intravenous pembrolizumab 200 mg once every 3 weeks, and oral trametinib 2 mg once daily or SBRT (same regimen) and intravenous gemcitabine (1000 mg/m 2 ) on day 1 and 8 of a 21-day cycle for eight cycles until disease progression, death, unacceptable toxicity, or consent withdrawal. The primary endpoint was overall survival in the intention-to-treat population. Safety was assessed in the as-treated population in all participants who received at least one dose of study treatment. This trial is registered with ClinicalTrials.gov, NCT02704156, and is now complete. Findings: Between Oct 10, 2016, and Oct 28, 2017, 198 patients were screened, of whom 170 patients were enrolled and randomly assigned to receive SBRT plus pembrolizumab and trametinib (n=85) or SBRT plus gemcitabine (n=85). As of the clinical cutoff date (Nov 30, 2020), median follow-up was 13·1 months (IQR 10·2–17·1). Median overall survival was 14·9 months (12·7–17·1) with SBRT plus pembrolizumab and trametinib and 12·8 months (95% CI 11·2–14·4) with SBRT plus gemcitabine (hazard ratio [HR] 0·69 [95% CI 0·51–0·95]; p=0·021). The most common grade 3 or 4 adverse effects were increased alanine aminotransferase or aspartate aminotransferase (ten [12%] of 85 in SBRT plus pembrolizumab and trametinib group vs six [7%] of 85 in SBRT plus gemcitabine group), increased blood bilirubin (four [5%] vs none), neutropenia (one [1%] vs nine [11%]), and thrombocytopenia (one [1%] vs four [5%]). Serious adverse events were reported by 19 (22%) participants in the SBRT plus pembrolizumab and trametinib group and 12 (14%) in the SBRT plus gemcitabine group. No treatment-related deaths occurred. Interpretation: The combination of SBRT plus pembrolizumab and trametinib could be a novel treatment option for patients with locally recurrent pancreatic cancer after surgery. Phase 3 trials are needed to confirm our findings. Funding: Shanghai Shenkang Center and Changhai Hospital. Translation: For the Chinese translation of the abstract see Supplementary Materials section.